Pertumbuhan dan Hasil Dua Varietas Mentimun dengan Pemberian Berbagai Dosis Pupuk Kandang Kotoran Itik di Lahan Rawa Lebak - Mahdiannoor Mahdiannoor; Nurul Istiqomah; Muhammad Ramlan (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2021)
Cucumber productivity fluctuates and tends to decrease due to suboptimal cultivation techniques such as the use of varieties and fertilization. Superior varieties are recommended to be planted because varieties improve production and yield quality. Manure in addition to improving physical properties and soil fertility can also keep soil moisture high in lebak wetland. This study aims to determine (i) the effect of the best interaction and interaction between two cucumber varieties and the dose of duck manure, (ii) the effect of single factor and the best two varieties of cucumber, (iii) the effect of single factor dose of duck manure and the best dose. . The research was conducted in March - June 2020 in Rantau Karau Hilir Village, Sungai Pandan District, Hulu Sungai Utara Regency. This study used a factorial randomized block design (RAK) consisting of the first factor of variety (v) namely v1 = Misano variety, v2 = Commander variety, the second factor was the dose of duck manure (d) namely d1 = 0 kg. plot-1 , d2 = 1 kg.plot-1, d3 = 2 kg.plot-1 , d4 = 3 kg.plot-1. The results showed that there was no interaction between cucumber varieties and the dose of duck manure. The single factor of two cucumber varieties had a very significant effect on the variables of plant length, the number of branches, flowering age, fruit weight of plots, and fruit length of plots except for the number of fruit plots. with the best variety Misano variety, The single factor of duck manure had a very significant effect on all observation variables with the best dose of 3 kg.plot-1 equivalent to 30/t.ha-1.